WebSphere Application Server 7.0 administration guide manage and administer your WebSphere Application Server to create a reliable, secure, and scalable environment for running your applications - Robinson, Steven Charles; Safari eBooks (Birmingham, U.K. : Packt Pub., 2009)
"This book will take you through the different methods for installing WebSphere application server and demonstrate how to configure and prepare WebSphere resources for your application deployments. During configuration you will be shown how to administer your WebSphere server standalone or using the new administrative agent, which provides the ability to administer multiple installations of WebSphere application server using one single administration console. WebSphere security is covered in detail showing the various methods of implanting federated user and group repositories. The facets of data-aware and message-aware applications are explained and demonstrated giving the reader real-world examples of manual and automated deployments. Key administration features and tools are introduced, which will help a WebSphere administrator manage and tune their WebSphere implementation and application for success"--Resource description page.
Description based on print version record.
Includes index.
Keywords: WebSphere; Web servers -- Computer programs; Application software -- Development; Electronic books